INDONESIA’S DEFENSE DIPLOMACY IN JOINT PRODUCTION OF HARIMAU MEDIUM TANK BETWEEN INDONESIA-TURKEY - Sereffina Yohanna Elisabeth; Sutrimo Sumarlan; Triyoga Budi Prasetyo; Jones Hutauruk (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2021)
Indonesia-Turkey defense diplomacy which aims to achieve self-sufficiency in defense equipment has resulted in the joint production of a medium tank called the Harimau or Kaplan. Each country requires a medium tank because this type of tank can operate in various geographical conditions found in Indonesia and Turkey. The purpose of this study is to examine the factors that contribute to the realization of joint production of tanks through the implementation of defense diplomacy strategies. Data were obtained through interviews with former Indonesian defense ministers for the period 2009-2014 as well as from the defense industry. In addition, secondary data was obtained from search results of official documents, official websites, and journals. Then the results of the interviews were analyzed descriptively. From this research, the factors that influence the cooperation between Indonesia and Turkey are obtained, namely the principle of equality, the principle of mutual trust and need, and the principle of business. In addition, Indonesia's defense diplomacy strategy is in the alignment of domestic and foreign defense policies, assessments, and maximizing the concepts of Government to Government (G to G) and Business to Business (B to B).